(untitled) (International Journal of Engineering and Computer Science, 2013)
This research study highlights energy savings that could be realized in an organization through various energy management options to reduce energy expenditure through efficient use of available energy resources. Energy audits were done as reference point for monitoring progress of measures put in place. It also reveals many opportunities for savings in coal usage, steam utilization and correction of electrical power factor. At the same time conserving the environment by reducing emission of greenhouse gases which pollute the environment.